Characteristic and the efficiency of fuel cell investigation using hydro genius teach - Muzamir, Isa; Baharuddin, Ismail; Ismail, Daut; Mohd Fayzul, Mohammed (Universiti Teknologi MARA (UiTM), 2008)
Organized by Universiti Teknologi Mara (UiTM) Cawangan Pulau Pinang, 8th - 9th December 2006 at UiTM Penang.